React 16 : the complete guide (incl. React Router 4 and Redux) (Packt Publishing, 2018)
"Learn React or dive deeper into it. Learn the theory, solve assignments, practice on demo projects and build one big application which is improved throughout the course: The Burger Builder! JavaScript is the major driver of modern web applications since it's the only programming language which runs in the browser and hence allows you to provide highly reactive apps. You'll be able to achieve mobile-app like user experiences in the web. But using JavaScript can be challenging - it quickly becomes overwhelming to create a nice web app with vanilla JavaScript and jQuery only. React to the rescue! React is all about components - basically custom HTML elements - with which you can quickly build amazing and powerful web apps. Just build a component once, configure it to your needs, dynamically pass data into it (or listen to your own events!) and re-use it as often as needed. Need to display a list of users in your app? It's as simple as creating a "User" component and outputting it as often as needed. By the end of the course, you will be able to build amazing React (single page) applications! A short refresher about the most important next-gen features is provided in the course."--Resource description page